Migration and differentiation potential of stem cells in the cnidarian Hydractinia analysed in eGFP-transgenic animals and chimeras - Künzel, Timo; Heiermann, Reinhard; Frank, Uri; Müller, Werner A.; Tilmann, Wido; Bause, Markus; Nonn, Anja; Helling, Matthias; Schwarz, Ryan S.; Plickert, Günter (Developmental biology, 2010)
To analyse cell migration and the differentiation potential of migratory stem cells in Hydractinia, we generated animals with an eGFP reporter gene stably expressed and transmitted via the germline. The transgene was placed under the control of two different actin promoters and the promoter of elongation factor-1α. One actin promoter (Act-II) and the EF-1α promoter enabled expression of the transgene in all cells, the other actin promoter (Act-I) in epithelial and gametogenic cells, but not in the pluripotent migratory stem cells. We produced chimeric animals consisting of histocompatible wild type and transgenic parts. When the transgene was under the control of the epithelial cell specific actin-I promoter, non-fluorescent transgenic stem cells immigrated into wild type tissue, stopped migration and differentiated into epithelial cells which then commenced eGFP-expression. Migratory stem cells are therefore pluripotent and can give rise not only to germ cells, nematocytes and nerve cells, but also to epithelial cells. While in somatic cells expression of the act-I promoter was restricted to epithelial cells it became also active in gametogenesis. The act-I gene is expressed in spermatogonia, oogonia and oocytes. In males the expression pattern showed that migratory stem cells are the precursors of both the spermatogonia and their somatic envelopes. Comparative expression studies using the promoters of the actin-II gene and the elongation factor-1α gene revealed the potential of transgenic techniques to trace the development of the nervous system.
Gesehen am 08.03.2023